2020
DOI: 10.3389/fmolb.2020.555372
|View full text |Cite
|
Sign up to set email alerts
|

New Insights on the Role of N6-Methyladenosine RNA Methylation in the Physiology and Pathology of the Nervous System

Abstract: RNA modifications termed epitranscriptomics represent an additional layer of gene regulation similar to epigenetic mechanisms operating on DNA. The dynamic nature and the increasing number of RNA modifications offer new opportunities for a rapid fine-tuning of gene expression in response to specific environmental cues. In cooperation with a diverse and versatile set of effector proteins that “recognize” them, these RNA modifications have the ability to mediate and control diverse fundamental cellular functions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 155 publications
(253 reference statements)
0
23
0
Order By: Relevance
“…Our results confirm that NSun2, one of the best described RNA methyltransferases in higher eukaryotes 56-, is expressed in the adult human brains (Figure 1). However, current understanding of the role that epitranscriptomic regulation plays in brain function and dysfunction is limited [63][64][65] . NSun2 deficiency has a negative impact on learning and memory in fruit flies and causes intellectual disability and neurological abnormalities in humans 62,66 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results confirm that NSun2, one of the best described RNA methyltransferases in higher eukaryotes 56-, is expressed in the adult human brains (Figure 1). However, current understanding of the role that epitranscriptomic regulation plays in brain function and dysfunction is limited [63][64][65] . NSun2 deficiency has a negative impact on learning and memory in fruit flies and causes intellectual disability and neurological abnormalities in humans 62,66 .…”
Section: Discussionmentioning
confidence: 99%
“…To date, several studies have implicated epitranscriptomic regulation of coding and non-coding RNA in diverse biological functions 65,70 . Here, we show NSun2 RNA methyltransferase protein levels are decreased in AD brains, denoting epitranscriptomic alterations in the AD process (Figure 1).…”
Section: Discussionmentioning
confidence: 99%
“…A genome-wide association study (GWAS) revealed that m6A dysfunction is linked to developing neurological disorders [107]. Furthermore, several studies have confirmed the role of m6A modification in the development of these disorders [108,109]. Altered m6A regulation could play an important role in the occurrence of Alzheimer's disease and its associated dementia [110,111].…”
Section: Conclusion and Prospectsmentioning
confidence: 99%
“…The developing and adult brain is characterized by the outgrowth of dendrites and axons of neurons known to form neural connections called synapses. Interestingly, synapses are enriched with m 6 A, which modulates dendrite formation (dendritogenesis), axonogenesis, and synaptic growth (synaptogenesis) and activity (reviewed in Li et al, 2019 ; Dermentzaki and Lotti, 2020 ). m 6 A-based transcriptome profiling of the mouse brain (cortex and cerebellum) showed enrichment of m 6 A modification linked to dendrite and dendritic spine, axon and axon guidance, and synaptogenesis and synaptic transmission ( Chang et al, 2017 ).…”
Section: N 6 -Methyladenosine Modification Prominently Regulates Brain Development and Functionmentioning
confidence: 99%
“…The massive prevalence of m 6 A in the developing and postnatal brain signifies the importance of m 6 A modification in regulating brain morphogenesis and function. Indeed, a chunk of the expanding knowledge indicating the phenomenal role of m 6 A in orchestrating neural development and function includes the proliferation of neural stem cells (NSCs) and other neural precursor cells, neuroprogenitor cell differentiation, gliogenesis, elaboration of neural processes, and synaptic transmission (reviewed in Widagdo and Anggono, 2018 ; Li et al, 2019 ; Chokkalla et al, 2020 ; Dermentzaki and Lotti, 2020 ; Livneh et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%